Pengaruh Penyuluhan (Ceramah dengan Power Point) terhadap Pengetahuan tentang Leptospirosis di Kecamatan Tembalang, Kota Semarang Jawa Tengah - Tri Wijayanti; Tri Isnani; Agung Puja Kesuma (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2016)
In Semarang City, leptospirosis mostly prevalent in Tembalang Sub District, particularly in the area of KedungmunduPublic Health Centre. Research of Epidemiology showed that 91 % of the community have lack knowledge about leptospirosis. Many risk factors of leptospirosis related with people behaviours, so they need more knowledge about it. Knowledge discourse can be done by media promotion. The objective of this research was to examine the effect of spreading information about leptospirosis with power point using LCD to the community. This research was quasi experiment design by pre-post test with control. The samples used 30 respondens as intervention group and the other 30 respondens as control group. Purposive sampling were use to get samples. Intervention was a discourse to addressleptospirosis using power point and LCD. The data obtained by interview the respondents before and a month after intervention. Data analyzed by Mann Whitney, Wilcoxon Signed Ranks Test and Kruskall Wallis. The result of this research showed that intervention could increase knowledge about leptospirosis in the community. Conclusion of this research was discourse with power point using LCD evidently increase community knowledge about leptopirosis and can be used as one of health promotion method.